Self-monitoring: An effectual classroom strategy / Norlaila Abdullah - Abdullah, Norlaila (2011)
This paper examines the effectiveness of self-monitoring (SMS) program in transforming students' misbehavior in classroom which if not overcome will eventually lead to sub-standard grade performance. The samples were the 36 students in Integrated Case Study (MAF680), a newly introduced code for Bachelor in Accountancy, who initially had shown some attitudinal and cognitive misbehavior in class. Following the seven (7) identified procedures, it was proven that SMS created huge positive variance not only in students' classroom behavioral abilities but also on the grade achievements where 83% of students obtained a grade point average (GPA) of 3.00 and above. Other benefits were observed such as making the students responsible by initiating control, checking, and applying prompt remedial measures with minimal effort from the lecturer and also making the lecturer more focused on content and strategy teaching that are vital in professional skills transfer.